IMPROVING EARLY CHILDHOOD’S ABILITY IN RECOGNIZING SYMBOLS OF NUMBER USING THE NUMBER CARD LEARNING MEDIA - Juandara, Eka Senja; Riyanto, Arifah A.; Noor, Agus Hasbi (Jurnal Empowerment, 2025)
This study seeks to find out the results of the Implementation of The Number Card Media Learning Model to Increase The Introduction of Number Symbols in Early Childhood. This research employed descriptive methodologies with a qualitative approach. The informants in the study comprised one ECE manager, two ECE educators, and eight ECE (PAUD) Mawar 1 students. Data collection approaches through interviews and observations. The study results indicated that the learning model using number cards can assist students develop as expected in their cognitive development specifically children can already recognize the symbol of numbers (numbers 1-10) and can already say the number symbol through the medium of number cards. With the medium of number cards, students look more interested in following the activities of recognizing the number symbol. The medium of number cards can facilitate the introduction of number symbols in early childhood.